Inequalities in maternal health: national cohort study of ethnic variation in severe maternal morbidities. - Knight, M; Kurinczuk, J; Spark, P; Brocklehurst, P (2009)
OBJECTIVE: To describe on a national basis ethnic differences in severe maternal morbidity in the United Kingdom. DESIGN: National cohort study using the UK Obstetric Surveillance System (UKOSS). SETTING: All hospitals with consultant led maternity units in the UK. PARTICIPANTS: 686 women with severe maternal morbidity between February 2005 and February 2006. MAIN OUTCOME MEASURES: Rates, risk ratios, and odds ratios of severe maternal morbidity in different ethnic groups. RESULTS: 686 cases of severe maternal morbidity were reported in an estimated 775 186 maternities, representing an estimated incidence of 89 (95% confidence interval 82 to 95) cases per 100 000 maternities. 74% of women were white, and 26% were non-white. The estimated risk of severe maternal morbidity in white women was 80 cases per 100 000 maternities, and that in non-white women was 126 cases per 100,000 (risk difference 46 (27 to 66) cases per 100 000; risk ratio 1.58, 95% confidence interval 1.33 to 1.87). Black African women (risk difference 108 (18 to 197) cases per 100,000 maternities; risk ratio 2.35, 1.45 to 3.81) and black Caribbean women (risk difference 116 (59 to 172) cases per 100 000 maternities; risk ratio 2.45, 1.81 to 3.31) had the highest risk compared with white women. The risk in non-white women remained high after adjustment for differences in age, socioeconomic and smoking status, body mass index, and parity (odds ratio 1.50, 1.15 to 1.96). CONCLUSIONS: Severe maternal morbidity is significantly more common among non-white women than among white women in the UK, particularly in black African and Caribbean ethnic groups. This pattern is very similar to reported ethnic differences in maternal death rates. These differences may be due to the presence of pre-existing maternal medical factors or to factors related to care during pregnancy, labour, and birth; they are unlikely to be due to differences in age, socioeconomic or smoking status, body mass index, or parity. This highlights to clinicians and policy makers the importance of tailored maternity services and improved access to care for women from ethnic minorities. National information on the ethnicity of women giving birth in the UK is needed to enable ongoing accurate study of these inequalities.